2024
DOI: 10.22354/24223794.1165
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Diseases in Colombia: Epidemiological Analysis Before and During the Universal Children Immunization against Streptococcus pneumoniae in the Light of a Vaccine Change in 2022

Carlos Torres-Martínez,
Germán Camacho-Moreno,
Jaime Patiño-Niño
et al.

Abstract: Streptococcus pneumoniae causes meningitis, pneumonia and bacteremia, mainly in children under 5 years of age and in the elderly. Pneumococcal conjugate vaccines (PCVs) have been administered globally since the year 2000, contributing to substantially reduce the incidence of pneumococcal diseases (PDs). In 2012, Colombia implemented universal vaccination with PCV10 in children under 2 years of age, achieving a decrease and stabilization of the incidence of PDs. However, since 2014, replacement of vaccine serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The most frequent serotype found during the study period was Spn19A (51.3%), whose proportion increased over time. The same phenomenon has been described in national surveillance data and in other studies conducted in Colombia ( 4–7 , 20 , 28–30 , 42 , 43 ) and elsewhere around the world after the universal administration of PCV10 ( 4 , 7 , 14 , 44–46 ). Serotypes Spn6C and Spn3 have also become more prevalent in all age groups, as has been observed in countries that have administered PCV10 ( 7 , 47 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The most frequent serotype found during the study period was Spn19A (51.3%), whose proportion increased over time. The same phenomenon has been described in national surveillance data and in other studies conducted in Colombia ( 4–7 , 20 , 28–30 , 42 , 43 ) and elsewhere around the world after the universal administration of PCV10 ( 4 , 7 , 14 , 44–46 ). Serotypes Spn6C and Spn3 have also become more prevalent in all age groups, as has been observed in countries that have administered PCV10 ( 7 , 47 ).…”
Section: Discussionsupporting
confidence: 81%
“…Streptococcus pneumoniae is the leading cause of meningitis and pneumonia in children under 5 years of age worldwide and causes 735,000 annual deaths from IPD ( 1 , 2 , 13 ). After the introduction of conjugate vaccines, the incidence of IPD has decreased, but it is crucial to continue with surveillance to monitor clinical behavior, the prevalence of serotypes, and bacterial resistance ( 1 , 4 , 20 , 27 ). This study showed that the majority of patients with IPD were under 24 months of age (40.5%), followed by the 24–59 months age group (38.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation